Impact of Genetic Polymorphisms on the Metabolic Pathway of Vitamin D and Survival in Non-Small Cell Lung Cancer - Laura Elena Pineda Lancheros (MDPI AG, 2021)
Vitamin D has been associated with risk, development, and progression of cancer. However, the genes involved in its metabolism are highly polymorphic, compromising its activity. The aim of this study is to evaluate the association between the gene polymorphisms involved in the metabolic pathway of vitamin D and survival in patients with non-small-cell lung cancer (NSCLC). The study was designed as an observational cohort which included 194 Caucasians patients from southern Spain with NSCLC. Real-time polymerase chain reaction was used to analyze the following polymorphisms: CYP27B1 rs4646536, rs3782130, and rs10877012; CYP24A1 rs6068816 and rs4809957; GC rs7041; CYP2R1 rs10741657; VDR rs1544410 (BsmI), rs11568820 (Cdx-2), rs2228570 (FokI), rs7975232 (ApaI), and rs731236 (TaqI). Progression-free survival (PFS) and overall survival were assessed. Cox regression showed that rs4646536 was associated with PFS in the general population (p = 0.0233) and in the non-resected NSCLC subgroup (p = 0.0233). In the resected NSCLC subgroup, rs11568820 was associated with OS (p = 0.0129) and rs7041 with PFS (p = 0.0447). In the non-resected NSCLC subgroup, rs6068816 was associated with PFS (p = 0.0048) and OS (p = 0.0089) and rs731236 and rs7975232 were associated with OS (p = 0.0005) and PFS (p = 0.0002), respectively. The other polymorphisms showed no effect on the results. The rs4646536, rs6068816, rs7041, rs11568820, rs731236, and rs7975232 polymorphisms are associated with survival in NSCLC and may have a substantial role as prognostic markers of the disease.